Understanding Interlayer Contact Conductance in Twisted Bilayer Graphene - Yu, Zhiwei; Song, Aisheng; Sun, Luzhao; Li, Yanglizhi; Gao, Lei; Peng, Hailin; Ma, Tianbao; Liu, Zhongfan; Luo, Jianbin (Small (Weinheim an der Bergstrasse, Germany), 2020)
Bilayer or few‐layer 2D materials showing novel electrical properties in electronic device applications have aroused increasing interest in recent years. Obtaining a comprehensive understanding of interlayer contact conductance still remains a challenge, but is significant for improving the performance of bilayer or few‐layer 2D electronic devices. Here, conductive atomic force microscope (C‐AFM) experiments are reported to explore the interlayer contact conductance between bilayer graphene (BLG) with various twisted stacking structures fabricated by the chemical vapor deposition (CVD) method. The current maps show that the interlayer contact conductance between BLG strongly depends on the twist angle. The interlayer contact conductance of 0° AB‐stacking bilayer graphene (AB‐BLG) is ≈4 times as large as that of 30° twisted bilayer graphene (t‐BLG), which indicates that the twist angle–dependent interlayer contact conductance originates from the coupling–decoupling transitions. Moreover, the moiré superlattice‐level current images of t‐BLG show modulations of local interlayer contact conductance. Density functional theory calculations together with a theoretical model reproduce the C‐AFM current map and show that the modulation is mainly attributed to the overall contribution of local interfacial carrier density and tunneling barrier. Interlayer contact conductance in twisted bilayer graphene is investigated by conductive atomic force microscopy in microscale and at moiré‐level. Combined with the simulated current map, the local moiré‐level current images suggest that the spots with high local conductance coincide with AA‐stacking regions, which is mainly determined by the interfacial carrier density.